Analysis of Multi-Carrier Code Division Multiple Access system under clipping noise in different channels - kumar, siva ness (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Multi Carrier Code Division Multiple Access (MC-CDMA), a promising technology for the 4G communication systems is considered in this paper. The foremost limitation of such system is the Multiple Access Interference (MAI) which is due to frequency-selective fading, near-far effect, frequency offset, and nonlinear power amplification.Â The performance of MC-CDMA under such scenario is poor . The Bit Error Rate (BER) performance is analyzed under clipping noise in a variety of channels, such as AWGN, Rayleigh fading and Rician channel as a function of Signal-to-Noise Ratio.